KONTRIBUSI PERILAKU PROKRASTINASI DALAM MEMPREDIKSI TINGKAT STRESS AKADEMIK PADA SISWA SEKOLAH MENEGAH PERTAMA - Kezia Ayu Teena; Lola Mustafa Loka; Wulan Rahmalia Permatasari; Deasyanti Deasyanti (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT The high tendency of academic procrastination among students has become a serious concern because it has the potential to increase academic stress arising from academic demands and learning workload. This study aims to examine the influence of academic procrastination on academic stress among junior high school students. This research employs a correlational quantitative design with simple linear regression analysis as the data analysis method. Purposive sampling technique was used to select the sample, consisting of 73 students from grades 7 to 9 at a private junior high school in South Tangerang. Data were collected through questionnaires using the Academic Expectations Stress Inventory (AESI) developed by Ang & Huan (2006) and the General Procrastination Scale (GP Scale) developed by Ferrari (2015). The results indicate a significant effect of academic procrastination on academic stress (R = 0.289; p = 0.013), where academic procrastination accounts for 8.4% of the variance in students' academic stress. Thus, the higher the level of academic procrastination among students, the higher the academic stress they experience, especially when facing school assignments and exams. ABSTRAK Tingginya kecenderungan prokrastinasi akademik pada peserta didik menjadi permasalahan serius karena berpotensi meningkatkan stres akademik yang bersumber dari tuntutan dan beban pembelajaran. Penelitian ini bertujuan untuk mengetahui pengaruh prokrastinasi akademik terhadap stres akademik pada siswa Sekolah Menengah Pertama (SMP). Penelitian ini merupakan penelitian kuantitatif korelasional dengan analisis regresi linier sederhana sebagai metode analisis data. Teknik pengambilan sampel menggunakan teknik purposive sampling. Sampel penelitian berjumlah 73 siswa SMP kelas 7 hingga 9 di salah satu sekolah swasta di Tangerang Selatan Pengumpulan data dilakukan dalam bentuk kuesioner dengan menggunakan instrumen Academic Expectations Stress Inventory (AESI) dan General Procrastination Scale (GP Scale). Hasil penelitian menunjukkan bahwa terdapat pengaruh signifikan antara prokrastinasi akademik terhadap stres akademik (R = 0,289; p = 0,013), di mana prokrastinasi akademik mampu menjelaskan sebesar 8,4% variasi stres akademik siswa. Dengan demikian, semakin tinggi tingkat prokrastinasi akademik siswa, maka semakin tinggi pula stres akademik yang mereka alami, terutama dalam menghadapi tugas dan ujian sekolah.